Quality rating of Islamic websites features : a single-user evaluation - Md. Tap, Abu Osman; Aliyu, Mansur; Mahmud, Murni (2010)
Islamic Websites post a new challenge for evaluation criteria due to the importance to their design contents. Today, little is known regarding the present quality rating of both design & content features of Islamic websites. This paper proposes several criteria to evaluate Islamic Websites: navigation, interactivity, legitimacy, objectivity, authority, relevance, attractiveness, credibility and reliability. A single-user evaluation has been conducted for fifty (50) selected Islamic Websites by using the proposed criteria. The results suggest that the quality of Islamic websites may change significantly over time. The findings also revealed that different design and content features contributes differently to the overall quality of Islamic websites. The paper suggests that the nine (9) identified criteria for both design and content features are suitable for the evaluation of different category of Islamic website's quality.